(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
This paper offers an analysis of masculinity in Natalia Ginzburg’s pièce, Ti ho sposato per allegria. A survey based on this same positioning has already been conducted by other scholars who have often studied writer’s novels and non-fiction production. From our point of view, the Ginzburg theatre deserves greater attention as a privileged place in which a revolutionary vision of the relationships between women and men is expressed. The analysis conducted with the lens of gender studies applied to literature will be able to add one more piece to the extensive study that has already been carried out on Ginzburg’s texts. We will begin by framing the play starting from the drafting of the list of characters’ peculiarities of those who are present and of those who are not; we will continue the study focusing on the speaking male characters - Pietro - and on those "spoken", that is, described and told in absentia by the people on stage. The final purpose of the contribution will be to give an account of the male characters of the text, often inadequate as they are removed from a stereotypical heroic, muscular and hegemonic dimension typical of the literary and non-literary tradition. Keywords: Natalia Ginzburg; theatre; gender studies; masculinity; comedy.